In-situ micro-nano TiC particle reinforced Cu-Cu3Ti composite material and preparation method thereof

Micron- and nanometer-sized TiC particles are generated at low temperatures through a pressureless sintering process, which solves the problems of complex and high-cost preparation processes of existing TiC-reinforced copper-based composite materials, and achieves the preparation of Cu-Cu3Ti composite materials with excellent performance.

CN119351820APending Publication Date: 2025-01-24SHANDONG UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411463341.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The preparation process of existing TiC reinforced copper-based composite materials is complex, has high cost, and is difficult to generate TiC particles of small particle size at low temperatures, affecting the wear resistance and electrical conductivity of the material.

Method used

In the atmosphere of non -pressure sintering, CU, Ti, and graphite are used to expose solid -phase diffusion in contact with each other, generating intervertebral metal compounds such as TIC and CU3TI, and controlling the sintering temperature to achieve a TIC particles of micron and nano -standard in situ.

Benefits of technology

The micro-nano TIC particles that are prepared under low-cost and easy-to-operate conditions are enhanced by the CU-CU3TI composite material, which improves the wear resistance and conductivity of the material, and is suitable for a variety of industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351820A_ABST
    Figure CN119351820A_ABST
Patent Text Reader

Abstract

The invention discloses an in-situ micro-nano TiC particle reinforced Cu-Cu3Ti composite material and a preparation method thereof, the in-situ micro-nano TiC particle reinforced Cu-Cu3Ti composite material is a composite material prepared by taking Cu powder, Ti powder and graphite powder as raw materials through pressureless sintering in-situ reaction, the composite material is composed of a Cu-Cu3Ti matrix phase and reinforced phase TiC, the reinforced phase TiC has two dimensions of micron and nanometer, and the particle size of the reinforced phase TiC is 2-5 microns. And the Cu-Cu3Ti nano-particles are uniformly dispersed and distributed in a Cu-Cu3Ti matrix to form a face-centered cubic structure. The TiC particles generated in situ by controlling the sintering temperature have two scales of micron and nanometer, are uniformly dispersed and distributed in a Cu-Cu3Ti matrix, have more excellent wear resistance compared with a single-scale TiC reinforced Cu-based composite material, and can be widely applied to the fields of rail transit, electrician and electronics, aerospace, military industry and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramic reinforced copper-based composite materials, and in particular to an in-situ micro-nano TiC particle reinforced Cu-Cu3Ti composite material and a preparation method thereof. Background Art

[0002] Copper and copper alloys are the third largest metal materials after steel and aluminum alloys. High-strength and high-conductivity copper alloys are widely used in communications, electrical, aviation, transportation and other fields, and play an important role in the development of modern industry. However, copper has relatively low strength and hardness, and poor wear resistance, which hinders the further development of copper. Particle-reinforced metal matrix composites combine the good ductility, electrical and thermal conductivity of the metal matrix with the high strength, high elastic modulus and high-temperature stability of ceramic particles. Among them, TiC is a very stable metal carbide with high melting point, high hardness, good wear resistance and corrosion resistance, making it one of the preferred materials for particle reinforcement phase. Introducing TiC into the Cu matrix to prepare TiC-Cu composites can achieve the regulation of the mechanical properties of copper-based alloys while maintaining high electrical conductivity. It is a composite material with good application prospects.

[0003] Chinese patent application No. 202210033629.0 discloses a Cu-TiC x The composite material and the preparation method thereof are firstly sintering raw material powder Ti3SiC2 powder and Ti3AlC2 powder into a porous skeleton by hot pressing sintering process, and then subjecting the copper block and the porous skeleton to high temperature infiltration treatment at 1100-1500°C to obtain Cu-TiC xComposite material. Chinese patent application No. 202110317786.X discloses a Cu-TiC electrical contact composite material and a preparation method thereof, using copper powder, titanium powder and graphite as raw materials, dividing the copper powder into two parts, firstly mixing the graphite powder with the first part of copper powder evenly under an argon atmosphere, and then fully mixing with the titanium powder and the remaining copper powder to obtain a Cu-Ti-graphite mixed powder, cold pressing, and then hot pressing sintering at a pressure of 100-300MPa, a sintering temperature of 850-950℃, and a sintering time of 0.5-2h. After sintering, the temperature is increased to 1050-1250℃, and a secondary hot pressing sintering is performed at a pressure of 300-700MPa, and the sintering time is 1-3h to obtain a finished composite material. Chinese patent application No. 201710301645.2 discloses a non-stoichiometric TiC reinforced copper-based composite material and a preparation method thereof, wherein Ti2SnC, Ti3SiC2 and Cu powders are vacuum in-situ reacted and sintered to prepare a non-stoichiometric TiC / Cu intermediate material; Cu is placed in a vacuum induction melting furnace, and after Cu is completely dissolved, Ni, TiC / Cu intermediate material, Sn and Si are sequentially added to the vacuum induction melting furnace for melting to obtain a non-stoichiometric TiC / Cu-Ni-Sn-Si powder material, and then the TiC / Cu-Ni-Sn-Si powder material is subjected to atomization treatment to obtain a pre-alloyed powder; the pre-alloyed powder is subjected to ball milling, cold pressing, vacuum sintering, extrusion and heat treatment to obtain a TiC / Cu-based composite material. The high-energy ball milling, hot pressing sintering and vacuum melting processes involved in the above-mentioned preparation process require high-cost special equipment, and the operation process is cumbersome, complicated and costly. Summary of the invention

[0004] In order to overcome the shortcomings of the prior art, the present invention provides an in-situ micro-nano TiC particle reinforced Cu-Cu3Ti composite material with excellent performance, simple preparation process and low cost and a preparation method thereof, so as to improve the hardness and wear resistance of the copper matrix.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] An in-situ micro-nano TiC particle reinforced Cu-Cu3Ti composite material is characterized in that it is composed of a Cu-Cu3Ti matrix phase and a reinforcing phase TiC, wherein the reinforcing phase TiC has two scales, micrometer and nanometer, and is uniformly dispersed in the Cu-Cu3Ti matrix, presenting a face-centered cubic structure.

[0007] Furthermore, the Cu-Cu3Ti matrix phase and the reinforcement phase TiC are obtained by in-situ reaction of Cu powder, Ti powder and graphite powder through pressureless sintering.

[0008] Furthermore, the pressureless sintering temperature is 1000-1150°C.

[0009] Furthermore, the mass fraction of Cu in the composite material is 20-80wt%, preferably 40-60wt%.

[0010] Furthermore, in order to improve the wettability of Cu to the in-situ TiC particles and promote the liquid phase sintering process, the molar ratio of C:Ti in the composite material is 0.5.

[0011] A method for preparing the above-mentioned in-situ micro-nano TiC particle reinforced Cu-Cu3Ti composite material is provided below, and the specific steps are as follows:

[0012] Step 1: Preparation of reaction body

[0013] Cu powder, Ti powder and graphite powder are used as raw materials, and a binder is added, mixed and evenly pressed into a green body;

[0014] Step 2 Preparation of composite materials

[0015] The green body is placed in a pressureless tube furnace and slowly heated in argon gas, kept at 600°C and 900°C for 1 hour respectively, and then kept at 1050-1100°C for 2 hours, so that chemical reactions occur between the components and micro-nano TiC particle-reinforced Cu-Cu3Ti composites are generated in situ.

[0016] Furthermore, the particle size of the Cu powder is 1-3 μm, and the purity is ≥99.9%; the particle size of the Ti powder is 1-3 μm, and the purity is ≥99.9%; the particle size of the graphite powder is 1-5 μm, and the purity is ≥99.9%.

[0017] Furthermore, the binder is formed by dissolving phenolic resin, polyvinyl butyral ester (PVB for short) or polyvinyl alcohol ester (PVA for short) in alcohol, preferably a 3wt.% PVB alcohol solution.

[0018] The present invention adopts a pressureless reaction sintering process to prepare an in-situ micro-nano TiC particle reinforced Cu-Cu3Ti composite material, which has the following beneficial effects compared with the existing composite materials and preparation processes:

[0019] (1) Since the pressureless reaction sintering process requires a high sintering temperature (generally above 1300°C) and a long holding time to prepare dense composite materials, the ceramic grains grow, making it difficult to prepare small-particle TiC. This makes it most common to use pressure sintering or smelting methods to prepare TiC-reinforced copper-based composite materials. The present invention controls the sintering temperature and adopts a low-cost, easy-to-operate and low-temperature pressureless reaction sintering process. In an argon atmosphere, Cu, Ti and graphite contact each other to undergo solid-phase diffusion to generate intermetallic compounds such as TiC, Cu3Ti, Cu4Ti3 and CuTi3. As the temperature rises, a Cu-Ti liquid phase is generated, liquid phase sintering begins, the green body shrinks, the density of the composite material increases, and a dense composite material is finally obtained.

[0020] (2) The TiC particles generated in situ by controlling the sintering temperature of the present invention have two scales, micrometer and nanometer, and are evenly dispersed in the Cu-Cu3Ti matrix. Compared with single-scale TiC reinforced Cu-based composite materials, they will have better wear resistance and can be widely used in rail transportation, electrical and electronic, aerospace and military industries.

[0021] (3) Compared with other in-situ synthesis technologies of TiC / Cu-based composite materials, the above process does not require additional high-energy ball milling and hot pressing sintering equipment. The process is simple and easy to operate, with low energy consumption, and is more suitable for mass production of composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following will briefly introduce the drawings required for the description of the embodiments. The drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. The following will clearly and completely describe the technical solutions of the embodiments of the present invention in conjunction with the drawings.

[0023] Figure 1 This is the XRD diagram of the micro-nano TiC reinforced Cu-Cu3Ti composite material prepared in Example 1 of the present invention.

[0024] Figure 2 TEM image of the micro-nano TiC reinforced Cu-Cu3Ti composite material prepared in Example 1 of the present invention; wherein (a) is the overall distribution diagram of the composite material, (b) is a local enlarged diagram of (a), (c) is the distribution diagram of the Cu element in the composite material, (d) is the distribution diagram of the C element in the composite material, and (e) is the distribution diagram of the Ti element in the composite material.

[0025] Figure 3The SEM images of particle sizes and corresponding particle size distribution diagrams of the micro-nano TiC reinforced Cu-Cu3Ti composite materials prepared in Example 1 of the present invention at different temperatures; (a) is the SEM image at 1000°C and the corresponding particle size distribution diagram, (b) is the SEM image at 1050°C and the corresponding particle size distribution diagram, (c) is the SEM image at 1100°C and the corresponding particle size distribution diagram, (d) is the SEM image at 1150°C and the corresponding particle size distribution diagram, and (e) is the SEM image at 1200°C and the corresponding particle size distribution diagram.

[0026] Figure 4 These are performance test diagrams of the micro-nano TiC reinforced Cu-Cu3Ti composite material prepared in Example 1 of the present invention; wherein (a) is a microhardness diagram of pure Cu and in-situ TiC-Cu-Cu3Ti composite material, (b) is a friction curve diagram of pure copper and in-situ TiC-Cu-Cu3Ti composite material, and (c) is a cross-sectional profile curve diagram of pure copper and in-situ TiC-Cu-Cu3Ti composite material. DETAILED DESCRIPTION

[0027] In order to enable those skilled in the art to better understand the scheme of the present invention, the following will be combined with the embodiments of the present invention and the attached Figure 1-2 , the technical solution of the present invention is further described in detail.

[0028] Example 1: Take the in-situ micro-nano TiC reinforced Cu-Cu3Ti composite material with a Cu volume fraction of 60% as an example.

[0029] ① Preparation of mixed powder: Cu powder (purity ≥ 99.9%, particle size 1 μm); Ti powder (purity ≥ 99.9%, particle size 1 μm); graphite powder (purity ≥ 99.9%, particle size 1-5 μm), the three powders and 3wt.% PVB were mixed uniformly with ethanol as solvent using a planetary ball mill, wherein the molar ratio of C:Ti was 0.5;

[0030] ② Preparation of green body: The mixed powder obtained in ① is loaded into a 10 mm × 10 mm mold, and a pressure of 8 MPa is applied to prepare a 10 mm × 10 mm square tablet sample to prepare a green body.

[0031] ③ Pressureless reaction sintering: Place the green body obtained in ② in a tubular furnace, and introduce pressureless argon gas for atmosphere protection, slowly heat up at a heating rate of 3℃ / min, and keep warm at 600℃ and 900℃ for 1h, then heat up to 1050℃ and keep warm for 2h to obtain in-situ micro-nano TiC particle reinforced Cu-Cu3Ti composite material with a relative density of 97.95%.

[0032] The phase composition of the in-situ micro-nano TiC reinforced Cu-based composite material prepared in Example 1 is as follows: Figure 1As shown, the microscopic morphology is Figure 2 As shown. Figure 1 It can be seen that the phase composition of the composite material includes TiC, Cu and Cu3Ti, without residual Ti and graphite, indicating that through the pressureless reaction sintering method, graphite and Ti react to form TiC, and the TiC-Cu-Cu3Ti composite material is successfully prepared. Figure 2 It can be seen that the TiC particles generated by the in-situ reaction are of two sizes, micrometer and nanometer, and are evenly distributed in the metal matrix, showing a face-centered cubic structure. The interface between the particles and the matrix is ​​clean, tightly combined, and has no agglomeration.

[0033] In order to demonstrate the importance of the sintering temperature in the preparation method of the present invention, a comparative test is given below to illustrate.

[0034] Five groups of comparative experiments were designed. The same formula was used. Except for the sintering temperatures of 1000°C, 1050°C, 1100°C, 1150°C and 1200°C, the other process parameters were the same as those in Example 1. The microstructure of the composite materials and the particle size distribution of TiC obtained from the five groups of comparative experiments are shown in FIG. Figure 3 As shown, combined Figure 3 (a)-3(d) It is found that micro-nano structures exist at 1000℃-1150℃. Figure 3 As can be seen from the particle size distribution diagram (e), when the temperature rises to 1200°C, the grains grow, the TiC nanostructure disappears, and the in-situ generated TiC particles only have a micron structure.

[0035] The hardness, friction coefficient and wear rate of the TiC-Cu-Cu3Ti composite material prepared in Example 1 are compared with those of pure copper. Figure 4 As shown in Table 1. Figure 4 (a) It can be seen that the average hardness of pure Cu is 52.39 HV, and the average hardness of the in-situ TiC-Cu-Cu3Ti composite is 631.52 HV. Due to the inherent hardness and strength of TiC, the presence of TiC particles can effectively serve as pinning sites in the composite structure, resulting in fine-grained reinforcement and improved performance of Cu. Figure 4 (b) It can be seen that the in-situ TiC-Cu-Cu3Ti composite material maintains a relatively stable friction coefficient of about 0.55 during the friction process, while the friction coefficient of pure Cu is about 0.74. Figure 4 (c) It can be seen that pure copper shows higher wear volume and wear depth during friction, while the in-situ TiC-Cu-Cu3Ti composite shows shallower and narrower wear marks. From Table 1, the wear volume and wear rate of pure Cu are 2.643×10 8 μm 3 and 2.94×10 5 μm 3 / N·m, while the wear volume and wear rate of the in-situ TiC-Cu-Cu3Ti composite were 1.247×10 8 μm 3 and 1.39×10 5 μm 3 / N·m, therefore, the tribological properties of the in-situ TiC-Cu-Cu3Ti composite are better than those of Cu.

[0036] Table 1

[0037] sample Friction work (N·m) <![CDATA[Wear volume (10 8 μm 3 )]]> <![CDATA[Wear rate (μm 3 / N·m)]]> Cu 900 2.643 <![CDATA[2.94×10 5 ]]> <![CDATA[TiC-Cu-Cu3Ti]]> 900 1.247 <![CDATA[1.39×10 5 ]]>

[0038] Table 2 lists the electrical conductivity of the in-situ TiC-Cu-Cu3Ti composite material obtained at three different sintering temperatures of the present invention. Theoretically, the electrical conductivity will increase with increasing sintering temperature, because the larger the particle size, the lower the degree of electron scattering. However, as can be seen from Table 2, the electrical conductivity at a sintering temperature of 1050°C is greater than the electrical conductivity at a sintering temperature of 1100°C. This shows that in practice, various factors should be comprehensively considered and a suitable sintering temperature should be selected so that the wear resistance and electrical conductivity of the obtained in-situ TiC-Cu-Cu3Ti composite material can be fully exerted.

[0039] Table 2

[0040] Sintering temperature℃ Sample size mm Resistance / Ω Resistivity ρ Conductivity 1 / ρ(S / m) 1000 9.14*9.18*1.46 5.71146E-05 3.28234E-06 304661.0525 1050 9.28*9.31*1.68 4.31572E-05 2.21943E-06 450565.9759 1100 9.20*9.09*1.76 5.12303E-05 2.43425E-06 410803.7011

[0041] The above is an embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An in-situ micro-nano TiC particle reinforced Cu-Cu3Ti composite material, characterized in that: It is composed of a Cu-Cu3Ti matrix phase and a reinforcing phase TiC. The reinforcing phase TiC has two scales, micrometer and nanometer, and is evenly dispersed in the Cu-Cu3Ti matrix, presenting a face-centered cubic structure.

2. The in-situ micro-nano TiC particle reinforced Cu-Cu3Ti composite material according to claim 1, characterized in that: The Cu-Cu3Ti matrix phase and the reinforcement phase TiC are obtained by in-situ reaction of Cu powder, Ti powder and graphite powder through pressureless sintering.

3. The in-situ micro-nano TiC particle reinforced Cu-Cu3Ti composite material according to claim 2, characterized in that: The pressureless sintering temperature is 1000-1150°C.

4. The in-situ micro-nano TiC particle reinforced Cu-Cu3Ti composite material according to claim 2, characterized in that: The mass fraction of Cu in the composite material is 20-80wt%.

5. The in-situ micro-nano TiC particle reinforced Cu-Cu3Ti composite material according to claim 4, characterized in that: The mass fraction of Cu in the composite material is 40-60wt%.

6. The in-situ micro-nano TiC particle reinforced Cu-Cu3Ti composite material according to claim 2, characterized in that: The molar ratio of C:Ti in the composite material is 0.

5.

7. A method for preparing an in-situ micro-nano TiC particle reinforced Cu-Cu3Ti composite material according to any one of claims 1 to 6, characterized in that: The specific steps are as follows: Step 1: Preparation of reaction body Cu powder, Ti powder and graphite powder are used as raw materials, and a binder is added, mixed and evenly pressed into a green body; Step 2 Preparation of composite materials The green body is placed in a pressureless tube furnace and slowly heated in argon gas, kept at 600°C and 900°C for 1 hour respectively, and then kept at 1050-1100°C for 2 hours, so that chemical reactions occur between the components and micro-nano TiC particle-reinforced Cu-Cu3Ti composites are generated in situ.

8. The method for preparing the in-situ micro-nano TiC particle reinforced Cu-Cu3Ti composite material according to claim 7, characterized in that: The particle size of the Cu powder is 1-3 μm, and the purity is ≥99.9%; the particle size of the Ti powder is 1-3 μm, and the purity is ≥99.9%; the particle size of the graphite powder is 1-5 μm, and the purity is ≥99.9%.

9. The method for preparing the in-situ micro-nano TiC particle reinforced Cu-Cu3Ti composite material according to claim 7, characterized in that: The adhesive is a 3wt.% PVB alcohol solution.

Citation Information

Patent Citations

  • Non-stoichiometric ratio TiC reinforced copper-based composite and preparation method thereof

    CN107119207A

  • Cu-TiC electric contact composite material and preparation method thereof

    CN113073226A

  • A Cu-TiC x Composite materials and their preparation methods

    CN114427049B